Implementation of Deep Learning Approach to English Learning in Elementary School - Sari, Ambar Wulan; Niswa, Khairun (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
One definition of deep learning is a strategy that prioritizes key knowledge application and conceptual comprehension. The goal of the research is to offer both theoretical and practical support for creating deep learning strategies that work in elementary school settings, particularly when it comes to teaching English. Observations, interviews, and an engineering triangulation approach are among the qualitative techniques employed. Teachers and elementary school pupils made up the study subjects. Through data reduction, data display, and conclusions, the gathered data is examined. The results of the study show that the application of Deep Learning to mathematical studies has a positive effect on students' understanding. This method encourages students' active involvement through various interactive activities, such as simulations and experiments, making the learning process more meaningful and enjoyable. However, the application of this method is also faced with a number of challenges, such as limited time to complete the curriculum and uneven access to technology among students